Hemoglobin Olympia (β20 Valine → Methionine): An Electrophoretically Silent Variant Associated with High Oxygen Affinity and Erythrocytosis - Stamatoyannopoulos, George; Nute, Peter E.; Adamson, John W.; Bellingham, A. J.; Funk, Donald (The Journal of Clinical Investigation, 1973)
In a family with erythrocytosis, electrophoretic and chromatographic studies failed to demonstrate a hemoglobin variant. However, the oxygen dissociation curves of affected individuals were shifted to the left of normal and this shift persisted when oxygen equilibria were studied in 2.3-diphosphoglycerate-stripped hemolysates. A mutant hemoglobin was evidently present in the red blood cells of the affected persons and was responsible for the increased oxygen affinity and erythrocytosis. Specific staining of tryptic peptide maps of β-chains from the propositus showed that peptide βT3 was positive for a sulfur-containing amino acid. Amino acid analysis yielded a composition identical to that of normal βT3, except that there were 2.6 residues of valine and 0.4 residues of methionine (normal composition: Val = 3.0, Met = 0). This suggested that the β-chains of affected individuals consisted of a mixture of two kinds of chains, 40% of which had a methionyl residue in βT3. Structural studies of isolated cyanogen bromide fragments demonstrated unequivocally that, in the abnormal β-chains, valine in position 20 is replaced by methionine. The new hemoglobin mutant is designated hemoglobin Olympia (β20 (B2) valine → methionine).